Powder containing niobium complex and lithium and its production method, and method of producing cathode active material for lithium ion batteries that has coating layer containing lithium niobate
Patent Information
- Application Number
- JP2022043244
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-28
- Filing Date
- 2022-03-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-03-17
AI Technical Summary
Existing lithium-ion secondary battery technologies face issues with high interfacial resistance and decreased performance due to the reaction between the positive electrode active material and solid electrolyte, and the precursor solutions for lithium niobate coatings have poor storage stability and high solvent-to-mass ratios, leading to high transportation costs.
A powder containing a niobium complex and lithium is developed, with specific composition and production methods to ensure high water solubility and stability, allowing for a lithium niobate coating on the positive electrode active material, reducing interfacial resistance and improving battery performance.
The high solubility of the niobium complex and lithium powder enables efficient formation of a lithium niobate coating, reducing high resistance layers and enhancing the performance of all-solid-state lithium-ion secondary batteries.
Abstract
Description
Technical Field
[0001] The present invention relates to a powder containing niobium complex lithium suitable for preparing an aqueous solution for coating the surface of positive electrode active material particles of a lithium ion secondary battery with lithium niobate as a solid electrolyte by a wet method, a method for producing the same, and a method for producing a lithium secondary battery positive electrode active material having a coating layer containing lithium niobate.
Background Art
[0002] The positive electrode active material of a lithium ion secondary battery is generally composed of a composite oxide of lithium and a transition metal. Among them, lithium cobaltate (LiCoO2), which is a composite oxide having Co as a component, is widely used. Recently, lithium nickelate (LiNiO2), lithium manganate (LiMn2O4), or a ternary system (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, etc.) and their composite types are also increasing in use.
[0003] As an electrolyte for a lithium ion secondary battery, a solution obtained by dissolving a lithium salt such as electrolyte LiPF6, LiBF4 in a mixed solvent of a cyclic carbonate such as PC (propylene carbonate), EC (ethylene carbonate) and a chain ester such as DMC (dimethyl carbonate), EMC (ethyl methyl carbonate), DEC (diethyl carbonate) is mainly used. Such organic solvents are vulnerable to an oxidizing atmosphere, and particularly tend to cause an oxidative decomposition reaction when touching transition metals such as Co, Ni, Mn, etc. on the positive electrode surface. As factors thereof, it is considered that the positive electrode surface has a high potential and the transition metal in a highly oxidized state acts catalytically. Therefore, it is effective to prevent contact between the electrolyte and the transition metal (for example, one or more of Co, Ni, Mn) constituting the positive electrode active material in maintaining the performance of the electrolyte.
[0004] As a method for fundamentally solving the problems of the above-described organic solvent-based electrolyte, a all-solid-state lithium ion secondary battery in which the electrolyte is replaced with a non-flammable solid electrolyte has been proposed. Generally, the electrode reaction of a battery occurs at the interface between the electrode active material and the electrolyte. Here, when a liquid electrolyte is used as the electrolyte, the electrolyte penetrates into the surface of the electrode active material present on the electrode, and a reaction interface for charge transfer is formed. In the case of an all-solid-state battery, a solid electrolyte having ionic conductivity serves as the electrolyte. However, since the solid electrolyte itself does not have fluidity like a liquid, it is necessary to mix the powder that becomes the electrode active material and the solid electrolyte or coat the powder that becomes the electrode active material with the solid electrolyte and pre-compound them before constructing the secondary battery.
[0005] However, in the case of an all-solid-state lithium ion secondary battery, there is a problem that the resistance (hereinafter sometimes referred to as "interface resistance") generated when lithium ions move at the interface between the positive electrode active material and the solid electrolyte increases, and the performance such as the battery capacity of the all-solid-state lithium ion secondary battery tends to deteriorate. The increase in the interface resistance is considered to be caused by the reaction between the positive electrode active material and the solid electrolyte to form a high-resistance site on the surface of the positive electrode active material. It is known that the interface resistance can be reduced by coating the surface of lithium cobaltate, which is the positive electrode active material, with lithium niobate. Various methods can be used for the coating method of lithium niobate. For example, in Patent Documents 1 to 4, a treatment liquid for forming a lithium niobate coating layer on the surface of lithium cobaltate, which is the positive electrode active material, using a wet method has been proposed.
Prior Art Documents
Patent Documents
[0006]
Patent Document 1
Patent Document 2
Patent Document 3
[0007] Patent Document 1 discloses an aqueous solution containing lithium and a niobium complex, with a pH value of 8.0 to 10.5, and a method for producing it. Patent Document 2 discloses a precursor solution for lithium niobate containing niobium polyate ions, Li ions, and hydrogen peroxide, and a method for producing it. Patent Document 3 discloses a solution containing lithium, a niobium complex, and nitrite, a method for producing the same, and a method for producing an active material for lithium secondary batteries using the said solution. All of the aqueous solutions disclosed in these patent documents are precursors for lithium niobate, and each patent document lists the storage stability of the aqueous solution as a problem to be solved. However, according to the inventors' research, none of the precursor solutions described in Patent Documents 1 to 3 necessarily provided satisfactory storage stability. In addition, these precursor aqueous solutions had the problem of high transportation costs due to the large proportion of solvent mass relative to the total mass.
[0008] Therefore, it is conceivable to dry and solidify a precursor solution of lithium niobate containing niobium and lithium, store it in a solid state, and dissolve it in water to make an aqueous solution when needed. However, powders containing niobium and lithium produced using conventional technology have the problem of low water solubility. In particular, the solubility of niobium in water is low, so a powder containing niobium and lithium with high water solubility has not been obtained.
[0009] For example, Patent Document 4 discloses a technique for obtaining lithium niobate by heating a precursor of lithium niobate, obtained by drying a solution containing niobium ions and lithium ions, at a temperature of 250°C to 300°C. However, the lithium niobate obtained by heating under these temperature conditions is poorly soluble in water.
[0010] In view of the above-mentioned problems, the present invention aims to provide a powder containing a niobium complex and lithium, which has high solubility in water, and a method for producing the same, which is suitable for preparing a precursor solution of lithium niobate for coating the surface of positive electrode active material particles of a lithium-ion secondary battery with lithium niobate, which is a solid electrolyte. Here, "niobium complex contained in the powder" refers to a solidified form in which niobium remains coordinately bonded with a ligand (complexing agent). Therefore, in this specification, the term niobium complex is used to mean both the complex formed in aqueous solution and the solidified form thereof, but the difference can be clearly understood from the context. [Means for solving the problem]
[0011] To achieve the above objectives, in the present invention, [1] A powder containing a niobium complex and lithium is provided, wherein the powder contains 25% by mass or more and 75% by mass or less of niobium, the proportion of niobium among the metal elements contained in the powder is 0.775% by mass or more and 0.950% or less, and the niobium dissolution rate of the powder containing the niobium complex and lithium, as defined by the following formula (1), is 80% or more. Niobium dissolution rate (%) = Nb w ×100 / Nb HF …(1) Here Nb w and Nb HF This is the mass of niobium, calculated using the following procedure. The powder containing the niobium complex and lithium is weighed, and the weighed powder is dissolved in 25°C water at 8 times its mass. The mixture is then filtered through a membrane filter with a mesh size of 0.20 μm, and the concentration of niobium in the resulting filtrate is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of niobium dissolved in the filtrate per unit mass of the weighed powder is calculated from the niobium concentration and mass of the filtrate obtained above, and this mass is then expressed as Nb w Let's assume that. Weigh a powder containing a niobium complex and lithium, add hydrofluoric acid to the weighed powder to dissolve it, and after cooling, measure the concentration of niobium in the obtained dissolved solution using an inductively coupled plasma atomic emission spectrometer (ICP - AES). The mass of niobium contained per unit mass of the weighed powder, calculated from the niobium concentration in the dissolved solution obtained above and the volume of the dissolved solution, is designated as Nb HF Let it be so. [2] The powder containing a niobium complex and lithium in item [1] preferably has a niobium content of 40% by mass or more and 50% by mass or less. [3] The powder containing a niobium complex and lithium in item [1] or [2] preferably contains 2.5% by mass or more and 6.0% by mass or less of lithium, and the total proportion of niobium and lithium among the metal elements contained in the powder is 0.80 or more and 1.00 or less in terms of mass ratio, and the molar ratio of Li / Nb is 0.7 or more and 1.5 or less. [4] The powder containing a niobium complex and lithium in items [1] to [3] preferably has a lithium content of 3.0% by mass or more and 4.5% by mass or less. [5] The powder containing a niobium complex and lithium in items [1] to [4] preferably has a lithium dissolution rate of 80% or more for the powder containing a niobium complex and lithium defined by the following formula (2). Here, Li w and Li HF are the masses of lithium calculated by the following procedure. Weigh a powder containing a niobium complex and lithium, dissolve the weighed powder in water at 25°C with a mass 8 times that of the powder, then filter it through a membrane filter with an aperture of 0.20 μm, and measure the concentration of lithium in the obtained filtrate using an inductively coupled plasma atomic emission spectrometer (ICP - AES). The mass of lithium eluted into the filtrate per unit mass of the weighed powder, calculated from the lithium concentration in the filtrate obtained above and the mass of the filtrate, is designated as Li w Let it be so. The niobium complex and lithium-containing powder are weighed, hydrofluoric acid is added to the weighed powder to dissolve it, and after cooling, the lithium concentration in the resulting solution is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of lithium contained per unit mass of the weighed powder is calculated from the lithium concentration and volume of the solution obtained above. HF Let's assume that. [6] The powders containing the niobium complex and lithium described in items [1] to [5] above contain oxygen, and it is preferable that the total content of niobium, lithium, and oxygen is 85% by mass or more. [7] The powder containing the niobium complex and lithium described in items [1] to [6] above is dissolved in eight times its mass in water at 25°C, and then filtered through a membrane filter with a mesh size of 0.20 μm. Preferably, the ammonium ion content in the obtained filtrate is 0.5% by mass or less. [8] The powder containing the niobium complex and lithium described in items [1] to [7] above is dissolved in eight times its mass of water at 25°C, and then filtered through a membrane filter with a mesh size of 0.20 μm. Preferably, the absorbance of the obtained filtrate at a wavelength of 660 nm is 1.0 or less. [9] The powders containing the niobium complex and lithium described in items [1] to [8] above have a cumulative 50% particle size D on a volume basis. 50 It is preferable that the diameter is 1 mm or less.
[0012] In the present invention,
[10] A method for producing a powder containing a niobium complex and lithium is provided, comprising the steps of: mixing a niobium compound, a lithium compound, an alkali, hydrogen peroxide, and water to obtain an aqueous solution containing a niobium complex and lithium; and drying the aqueous solution containing the niobium complex and lithium at a temperature below the decomposition temperature of the niobium complex.
[11] In the method for producing the powder containing the niobium complex and lithium described in item
[10] above, it is preferable that the pressure of the aqueous solution during drying is less than or equal to the saturated vapor pressure of water at the drying temperature of the aqueous solution. In the present invention, further,
[12] A method for producing a lithium secondary battery positive electrode active material having a coating layer containing lithium niobate is provided, comprising the steps of: dissolving the powder containing niobium complex and lithium obtained by the method for producing a powder containing niobium complex and lithium according to item
[10] or
[11] in water to obtain an aqueous solution containing niobium complex and lithium; coating the surface of a lithium secondary battery positive electrode active material with the aqueous solution containing niobium complex and lithium; and heat treating the lithium secondary battery positive electrode active material coated with the aqueous solution containing niobium complex and lithium. [Effects of the Invention]
[0013] A precursor solution of lithium niobate can be easily obtained by dissolving a powder containing a niobium complex and lithium, obtained by the manufacturing method of the present invention, in water. A lithium niobate coating layer formed on the surface of a positive electrode active material for a lithium-ion secondary battery using this precursor solution does not form a high-resistance layer. Therefore, the present invention can contribute to improving the performance of all-solid-state lithium-ion secondary batteries. [Modes for carrying out the invention]
[0014] [Cathode active material] The positive electrode active material coated with a precursor solution of lithium niobate, prepared from a powder containing the niobium complex and lithium of the present invention, is, for example, the following. The positive electrode active material consists of a composite oxide of Li and a transition metal M, and is a material that has been conventionally used in lithium-ion secondary batteries, for example, lithium cobalt (Li 1+X CoO2 (-0.1 ≤ X ≤ 0.3), Li 1+X KiO2, Li 1+X Mn2O4, Li 1+X Ni 1 / 2 Mn 1 / 2 O2, Li 1+X Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (both -0.1 ≤ X ≤ 0.3), Li 1+X [Ni Y Li 1 / 3-2Y / 3 Mn 2 / 3-Y / 3O2 (0 ≦ X ≦ 1, 0 < Y < 1 / 2), lithium transition metal oxides in which some of these Li or transition metal elements are substituted with Al or other elements, Li 1+X FePO4, Li 1+X Phosphates having an olivine structure such as MnPO4 (both -0.1 ≦ X ≦ 0.3) can be mentioned.
[0015] [Powder containing a niobium complex and lithium] In the present invention, a powder containing a niobium complex and lithium for preparing a precursor solution of lithium niobate is provided. The powder contains niobium, lithium, and inevitable impurities resulting from the manufacturing process as metal elements. The content of niobium in the powder is preferably 25% by mass or more and 75% by mass or less.
[0016] The niobium content in the precursor solution of lithium niobate is set according to the design of battery units such as the positive electrode active material. However, as the powder, the higher the niobium content, the easier the concentration adjustment by subsequent dilution with water and the wider the adjustment range. Therefore, the content of niobium in the powder is preferably 25% by mass or more, and more preferably 40% by mass or more. Further, since the powder contains lithium, oxygen, components of a complexing agent, etc. as constituent components, the upper limit of the niobium content in the powder does not exceed 75% by mass. The content of niobium in the powder is more preferably 50% by mass or less.
[0017] The ratio of niobium to the metal elements in the powder is preferably 0.775 to 0.950 by mass. If the ratio of niobium to the metal elements is less than 0.775, the ratio of lithium will be excessive, or the content of metal elements other than niobium and lithium will be high. If the ratio of lithium is excessive, when a lithium niobate precursor solution is prepared using the powder and a coating layer is formed on the positive electrode active material, components that do not conduct lithium ions, such as lithium hydroxide, will be generated, which is undesirable as it will worsen battery performance. Similarly, if the content of metal elements other than niobium and lithium is high, when a lithium niobate precursor solution is prepared using the powder and a coating layer is formed on the positive electrode active material, components that do not conduct lithium ions will be generated, which is undesirable as it will worsen battery performance. Furthermore, if the ratio of niobium to the metal elements exceeds 0.950, the Li / Nb molar ratio described later will be less than 0.7, which is undesirable.
[0018] It is preferable that the niobium contained in the powder forms a complex. The formation of this complex improves the solubility of niobium in water. The presence or absence of niobium complex formation can be determined by Fourier transform infrared spectroscopy (FT-IR) by measuring the amount of 845±20 cm² attributable to the complex. -1 This is confirmed by the presence of an absorption peak. The niobium content in the powder will be discussed later.
[0019] [Water soluble] As described above, the powder containing the niobium complex and lithium obtained by the present invention has high solubility in water, i.e., high water solubility. In particular, it is a powder with high solubility of niobium, which has low solubility in water. In this specification, water solubility is evaluated by the niobium solubility of the powder containing the niobium complex and lithium defined by the following formula (1). Niobium dissolution rate (%) = Nb w ×100 / Nb HF …(1) Here Nb w and Nb HF This is the mass of niobium, calculated using the following procedure. The powder containing the niobium complex and lithium is weighed, and the weighed powder is dissolved in 25°C water at 8 times its mass. The mixture is then filtered through a membrane filter with a mesh size of 0.20 μm, and the concentration of niobium in the resulting filtrate is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of niobium dissolved in the filtrate per unit mass of the weighed powder is calculated from the niobium concentration and mass of the filtrate obtained above, and this mass is then expressed as Nb w Let's assume that.
[0020] The powder containing the niobium complex and lithium is weighed, hydrofluoric acid is added to the weighed powder to dissolve it, and after cooling, the concentration of niobium in the resulting solution is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of niobium contained per unit mass of the weighed powder is calculated from the niobium concentration and volume of the solution obtained above, and this mass is Nb HF Let's assume that. From these two values, the niobium dissolution rate (Nb w ×100 / Nb HF The following is calculated and used as an indicator of the water solubility of the powder containing the niobium complex and lithium:
[0021] In the powder containing the niobium complex and lithium of the present invention, the niobium dissolution rate, as defined by formula (1) above, is 80% or more. If the niobium dissolution rate is less than 80%, insoluble solids containing niobium will be included in the prepared lithium niobate precursor solution. If these solids are mixed into the lithium niobate coating layer ultimately formed on the surface of the positive electrode active material, the thickness of the coating layer will become uneven, leading to the formation of high-resistance areas from the thin film portion, which can degrade battery performance and is therefore undesirable.
[0022] The powder containing the niobium complex and lithium of the present invention is ultimately used to form a lithium niobate coating layer on the surface of the positive electrode active material; therefore, the amounts of lithium and niobium added need to be close to equimolar.
[0023] The powder containing the niobium complex and lithium of the present invention preferably contains 2.5% by mass or more and 6.0% by mass or less lithium, and more preferably 3.0% by mass or more and 4.5% by mass or less lithium. If the lithium content in the powder is less than 2.5% by mass, the proportion of components that are not needed as raw materials for the lithium niobate precursor solution increases, which is undesirable because it increases transportation costs. Furthermore, since the powder contains niobium, oxygen, complexing agent components, etc. as constituent components, the upper limit of the lithium content in the powder does not exceed 6.0% by mass.
[0024] Furthermore, it is preferable that the total proportion of niobium and lithium in the powder is 0.80 or more and 1.00 or less by mass ratio. If the total proportion of niobium and lithium in the powder is less than 0.80 by mass ratio, the proportion of unnecessary components in the mass of the lithium niobate precursor solution increases, which is undesirable because it increases transportation costs. The molar ratio of niobium to lithium, Li / Nb, is preferably 0.7 or more and 1.5 or less. If Li / Nb is less than 0.7, lithium is deficient in the lithium niobate represented by LiNbO3, which is undesirable because it worsens the lithium ion conductivity in the final lithium niobate film. Also, if Li / Nb exceeds 1.5, when preparing the precursor solution, the pH rise due to excess lithium hydroxide worsens the storage stability of the solution, which is undesirable. The niobium and lithium content mentioned above can be measured by following the method described later in [Measurement of Niobium and Lithium Content].
[0025] The water solubility of the powder containing the niobium complex and lithium of the present invention can also be defined by the lithium solubility of the powder containing the niobium complex and lithium, as defined by formula (2) below. In the powder containing the niobium complex and lithium of the present invention, it is preferable that the lithium solubility is 80% or more. Lithium dissolution rate (%) = Li w ×100 / Li HF …(2) Here Li w and Li HFThis is the mass of lithium calculated using the following procedure. The niobium complex and lithium-containing powder are weighed, and the weighed powder is dissolved in 25°C water at 8 times its mass. The mixture is then filtered through a membrane filter with a mesh size of 0.20 μm, and the lithium concentration in the resulting filtrate is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The amount of lithium dissolved into the filtrate per unit mass of the weighed powder is calculated from the lithium concentration and mass of the filtrate obtained above. w Let's assume that.
[0026] The niobium complex and lithium-containing powder are weighed, hydrofluoric acid is added to the weighed powder to dissolve it, and after cooling, the lithium concentration in the resulting solution is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of lithium contained per unit mass of the weighed powder is calculated from the lithium concentration and volume of the solution obtained above. HF Let's assume that.
[0027] If the lithium dissolution rate is less than 80%, the prepared lithium niobate precursor solution will contain insoluble solids, including niobium or lithium. If these solids are mixed into the lithium niobate coating layer that is ultimately formed on the surface of the positive electrode active material, the thickness of the coating layer will become uneven, leading to the formation of high-resistance areas from the thin film portion, which can degrade battery performance and is therefore undesirable.
[0028] The powder containing the niobium complex and lithium of the present invention contains oxygen in addition to niobium and lithium, and it is preferable that the total content of niobium, lithium, and oxygen is 85% by mass or more. The powder also contains other hydrogen due to hydrogen peroxide, but the mass of hydrogen is negligibly small, so the upper limit of the total content of niobium, lithium, and oxygen can be close to 100% by mass. The oxygen content of the powder containing the niobium complex and lithium is the value of the oxygen concentration (by mass) measured using an oxygen / nitrogen analyzer, as described in the [Measurement of Carbon and Oxygen Content] section of the examples below.
[0029] The powder containing the niobium complex and lithium of the present invention preferably has a carbon content of 0.5% by mass or less. If the carbon content is greater than 0.5% by mass, there is a higher possibility that lithium carbonate will be formed when the lithium niobate coating layer is ultimately formed on the surface of the positive electrode active material. Since lithium carbonate does not have lithium ion conductivity, it may degrade battery performance and is therefore undesirable. The carbon concentration in the dried powder sample is measured using the trace carbon and sulfur analyzer described in the [Measurement of Carbon and Oxygen Content] section of the examples below.
[0030] Furthermore, it is preferable that the ammonium ion content in the filtrate obtained by dissolving the powder containing the niobium complex and lithium of the present invention in eight times its mass of water at 25°C, and then filtering it through a membrane filter with a mesh size of 0.20 μm, is 0.5% by mass or less. It is preferable that the ammonium ion content in the filtrate is 0.5% by mass or less, as this stabilizes the niobium complex in the precursor solution of lithium niobate, which is an aqueous solution containing the niobium complex and lithium after dissolving the powder containing the niobium complex and lithium in water, and suppresses the decomposition of the niobium complex and the precipitation of water-insoluble solids. The ammonium ion content in the filtrate solution is measured using the ion chromatograph described in [Measurement of Ammonium Ion Content in Filtrate] in the Examples described later.
[0031] The powder containing the niobium complex and lithium of the present invention is dissolved in eight times its mass of water at 25°C, and then filtered through a membrane filter with a mesh size of 0.20 μm. The resulting filtrate contains insoluble fine particles that have passed through the 0.20 μm membrane filter, and the amount of these fine particles can be qualitatively evaluated by the absorbance at a wavelength of 660 nm. It is preferable that the absorbance at a wavelength of 660 nm of the filtrate obtained after dissolving the powder containing the niobium complex and lithium of the present invention in eight times its mass of water at 25°C and filtering through a membrane filter with a mesh size of 0.20 μm is 1.0 or less. Note that the insoluble fine particles that have passed through this membrane filter are included in the amount of solubility defined as water solubility.
[0032] Furthermore, the powder containing the niobium complex and lithium of the present invention has a cumulative 50% particle size D based on volume after crushing. 50 It is preferable that it is 1 mm or less. 50 If the particle size exceeds 1 mm, solubility in water decreases, and there is a high possibility that undissolved powder particles will be included as solids in the prepared lithium niobate precursor solution, which is undesirable. 50 There is no particular lower limit to the preferred size, but typically sizes of 10 μm or larger are obtained. Therefore, D 50 The range is preferably 10 μm to 1 mm. 50 This is measured using a laser diffraction scattering particle size distribution analyzer. The dried powder sample containing the above-mentioned niobium complex and lithium contains moisture. The amount of moisture can be measured by coulometric titration using the Karl Fischer method, and is usually less than 20% by mass. Furthermore, based on the TG-DTA measurement results, this moisture is considered to be crystal water, not adhering water.
[0033] The powder containing the niobium complex and lithium of the present invention preferably contains an amorphous substance. Here, containing an amorphous substance means that the powder containing the niobium complex and lithium does not have a distinct crystalline structure. When the powder containing the niobium complex and lithium contains water as a component, the powder is more likely to become amorphous. It is preferable that the powder contains an amorphous substance because its solubility in water increases, and the possibility of undissolved powder being included as solid matter in the prepared lithium niobate precursor solution is reduced. Note that the powder containing the niobium complex and lithium of the present invention does not need to be amorphous as a whole; it is sufficient if a part of it takes on an amorphous structure. Whether a powder containing niobium complex and lithium contains amorphous materials can be determined by whether a halo pattern is observed in the diffraction pattern obtained by X-ray diffraction measurement in the region 2θ:20° to 60° (when a Cu X-ray tube is used for measurement). Here, "halo" refers to a broad elevation observed in the diffraction pattern without a clear peak. In this invention, a broad elevation with a full width at half maximum of 2θ:2° or more is defined as a halo.
[0034] [Method for producing a powder containing niobium complex and lithium] [Raw material solution] In the present invention's method for producing a powder containing a niobium complex and lithium, a niobium compound, a lithium compound, and hydrogen peroxide and an alkali, which are complexing agents (ligands) for solubilizing the niobium complex in an aqueous solution, are mixed in water to obtain a raw material solution (starting material) which is an aqueous solution containing the niobium complex and lithium.
[0035] The ligand for the niobium complex described above can be any ligand that makes the niobium complex water-soluble, and there are no particular restrictions. However, in this embodiment, hydrogen peroxide is used as the ligand, and the peroxo complex of niobic acid ([Nb(O2)4] 3- ) is formed. Since the peroxo complex of niobate does not contain carbon in its chemical structure, no carbon remains in the lithium niobate coating film that is ultimately produced, making it particularly suitable for the method of producing a powder containing the niobate complex and lithium of the present invention. The peroxo complex of the niobic acid can be obtained, for example, by the following method. Hydrated niobium oxide (Nb2O5·nH2O) is added to hydrogen peroxide solution and mixed. In this mixture, niobium does not dissolve in hydrogen peroxide solution, but a milky white suspension solution can be obtained.
[0036] A transparent niobate peroxo complex can be obtained by adding an alkali such as aqueous ammonia to a suspension of the niobate peroxo complex and mixing it. The amount of alkali added to the suspension should be such that the pH of the final solution containing the niobium complex and lithium is between 8.0 and 11.5, as will be described later. Furthermore, when adding aqueous ammonia as an alkali to the suspension, the amount of aqueous ammonia to be added should be determined considering that ammonia will volatilize during the reaction. Alternatively, an alkaline solution can be added instead of the ammonia solution. A lithium hydroxide aqueous solution can be selected and added as the alkaline solution.
[0037] [Niobium compounds] Since anhydrous niobium oxide (Nb2O5) is sparingly soluble in water, the manufacturing method of the present invention uses amorphous, water-soluble hydrated niobium oxide as the Nb source. Hydrated niobium oxide is a substance represented by the general formula Nb2O5·nH2O (where n is not 0, but for example, 3≦n≦16). While the present invention does not specifically specify the concentration of niobium in the raw material solution, from the viewpoint of manufacturability, it is preferable that the concentration of niobium be between 0.1 mol / L and 10.0 mol / L.
[0038] [Lithium compounds] In the manufacturing method of the present invention, lithium hydroxide (LiOH) is used as the Li compound. LiOH can be either anhydrous or hydrated. LiOH added to an aqueous solution is Li + and OH - It dissociates and exhibits strong alkalinity. Since LiOH is itself strongly alkaline, when LiOH is added to an aqueous solution containing niobic acid, the pH of the system rises and the niobium oxide dissolves. Subsequently, hydrogen peroxide is added to the alkaline aqueous solution containing niobium and Li ions to form a niobium peroxo complex. The amount of Li added to the raw material solution should be such that the Li / Nb molar ratio is between 0.7 and 1.5. The reason for this has been explained previously.
[0039] [hydrogen peroxide] In the method for producing a powder containing a niobium complex and lithium according to the present invention, hydrogen peroxide is added to the raw material solution to complex the niobium and form a peroxo complex in order to ensure the water solubility of the powder and to ensure the stability of the powder when dissolved in water. The concentration of hydrogen peroxide added is preferably 2 moles or more and 25 moles or less per mole of niobium. More preferably 4 moles or more and 20 moles or less. If the concentration of hydrogen peroxide is less than 3 moles per mole of niobium, the niobium cannot form a peroxo complex, which is undesirable. Also, if it exceeds 25 moles, unreacted hydrogen peroxide remains in the raw material solution, which is undesirable because it deteriorates the stability of the niobium complex.
[0040] [pH] As mentioned above, since LiOH is a strong alkali, the raw material solution becomes alkaline. The pH of the raw material solution is preferably 8.0 to 11.5 to prevent destabilization of the niobium complex. In order to adjust the pH of the raw material solution to this range, additional alkalis other than LiOH may be added. In that case, it is preferable to add aqueous ammonia or ammonium carbonate, which are less likely to remain as impurities in the powder containing the niobium complex and lithium. Note that the pH value here is measured using a glass electrode with a pH meter equipped with a temperature-compensated electrode, calibrated using an appropriate buffer solution according to the pH range to be measured, based on JIS Z8802. Furthermore, when the powder containing the niobium complex and lithium obtained by the manufacturing method of the present invention is dissolved in eight times its mass in water at 25°C, it is preferable that the ammonium ion content in the filtrate is 0.5% by mass or less.
[0041] [Drying process] In the method for producing a powder containing a niobium complex and lithium according to the present invention, the raw material solution prepared under the above conditions is dried at a temperature below the decomposition temperature of the niobium complex to obtain the powder. The decomposition temperature of the niobium complex is determined by conducting preliminary experiments using thermogravimetric-suggestive thermal analysis (TG-DTA) for each preparation condition of the raw material solution, detecting the temperature of the endothermic peak, and defining this as the decomposition temperature. Drying at atmospheric pressure below the decomposition temperature of the niobium complex results in a slow solvent evaporation rate, leading to decreased productivity. Therefore, from a productivity standpoint, it is preferable to dry the raw material solution at a temperature below the saturated vapor pressure of water at the drying temperature of the raw material solution. Furthermore, if the decomposition temperature of the niobium complex is below 100°C, crystal water may remain in the powder containing the niobium complex and lithium after drying. The amount of this crystal water can be measured by coulometric titration using the Karl Fischer method. The amount of crystal water is acceptable if it is 20% by mass or less.
[0042] The resulting dried powder may be crushed. The crushing method is not particularly limited, but for example, it can be crushed using a mortar and pestle.
[0043] [Method for manufacturing the positive electrode active material of a lithium secondary battery] A lithium secondary battery positive electrode active material coated with lithium niobate can be produced by the following steps: dissolving the powder containing the niobium complex and lithium obtained by the method for producing a powder containing the niobium complex and lithium in water to obtain a precursor solution of lithium niobate, which is an aqueous solution containing the niobium complex and lithium; coating the surface of a lithium secondary battery positive electrode active material with the aqueous solution containing the niobium complex and lithium; and heat-treating the lithium secondary battery positive electrode active material coated with the aqueous solution containing the niobium complex and lithium. For specific manufacturing conditions, the methods described in Patent Documents 1 to 4 or known methods can be used. [Examples]
[0044] [Qualitative evaluation of niobium complexes] The presence or absence of niobium complex in the powder was determined using the single-reflection ATR method of Fourier transform infrared spectroscopy (FT-IR). Specifically, the dried powder samples obtained in the examples were measured using a Thermo Fisher NICOLET6700 FT-IR instrument and a single-reflection ATR accessory Smart OMNI-Sampler (germanium crystal, incident angle 45°) with 16 scans and a resolution of 4. Ion-exchanged water was used for background measurement. The measured spectrum was subjected to automatic baseline correction using the analysis software (OMNIC Specta) included with the FT-IR instrument NICOLET6700, followed by one auto-smoothing step. Peak detection was then performed at a sensitivity of 50, at wavenumber 845 cm⁻¹. -1 ±20cm -1 When a peak was observed, it was determined that the measured powder contained a niobium complex.
[0045] [Measurement of niobium and lithium content] For powdered samples, such as the dried powder sample obtained in the examples, approximately 0.1 g of the dried powder sample was accurately weighed, and a small amount of pure water and 1 mL of 46% by mass hydrofluoric acid were added to the powder sample. The mixture was then heated and dissolved on a hot plate at approximately 140-170°C. After the solution was cooled to room temperature at approximately 20-30°C, it was brought to a fixed volume using a volumetric flask, diluted as appropriate, and the niobium and lithium concentrations of the diluted solution were measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Agilent Technologies, Inc. CP-720). The niobium and lithium content of the dried powder sample was then calculated. Furthermore, for samples in solution form, such as raw material solutions, 0.1 g of the solution sample was taken, 15 ml of pure water and 5 ml of hydrochloric acid were added, and then 2 ml of hydrogen peroxide solution was added to obtain a solution in which niobium and lithium were dissolved, after which the subsequent operations were carried out.
[0046] [Evaluation of water solubility] The mass of niobium and lithium eluted in the filtrate obtained by filtering an aqueous solution prepared by dissolving a unit mass of the dried powder obtained in the example in water at 25°C (Nb in formulas (1) and (2) below)w and Li w ) and the mass of niobium and lithium contained in the dried powder obtained in the examples (Nb in formulas (1) and (2) below) HF and Li HF From this, the niobium dissolution rate and lithium dissolution rate, defined by equations (1) and (2) below, were calculated. Specifically, the niobium dissolution rate and lithium dissolution rate were calculated using the following procedure.
[0047] <1> 1.0 g or 2.0 g of the dried powder sample obtained in the example was accurately weighed, dissolved in 8 times its mass (8.0 g or 16.0 g) of water at 25°C, and the solution was filtered using a membrane filter (DISMIC-25HP, manufactured by Toyo Roshi Co., Ltd., with a mesh size of 0.20 μm). <2> the above <1> The concentrations of niobium and lithium in the filtrate obtained were measured using the same method as for the sample in solution state. From the measured values and the mass of the obtained filtrate, the mass of niobium and lithium dissolved in the filtrate from a unit mass of powder dissolved in water at 25°C (Nb in equations (1) and (2) below) was calculated. w and Li w ) was calculated. <3> The masses of niobium and lithium contained in the dried powder samples obtained in the examples were measured using the same measurement method as for the powder samples described above. From these measured values and the mass of the weighed dried powder samples, the mass of niobium and lithium contained in a unit mass of dried powder (Nb in equations (1) and (2) below) was calculated. HF and Li HF ) was calculated. <4> the above <2> and the above <3> Nb obtained w Li w Nb HF and Li HF From these values, the niobium dissolution rate and lithium dissolution rate, as defined by equations (1) and (2) below, were calculated. Niobium dissolution rate (%) = Nb w ×100 / Nb HF …(1) Lithium dissolution rate (%) = Li w ×100 / Li HF …(2)
[0048] [Measurement of carbon and oxygen content] The carbon concentration in the dried powder sample was measured using a trace carbon-sulfur analyzer (ETMA-U510, Horiba, Ltd.), and the oxygen concentration was measured using an oxygen-nitrogen analyzer (EMGA-920, Horiba, Ltd.).
[0049] [Measurement of ammonium ion content in filtrate] 1.0 g or 2.0 g of the dried powder sample obtained in the examples was accurately weighed and dissolved in 8 times its mass (8.0 g or 16.0 g) of water at 25°C. The solution was then filtered using a membrane filter (DISMIC-25HP, manufactured by Toyo Roshi Co., Ltd., with a mesh size of 0.20 μm), and the amount of ammonium ions in the resulting filtrate was measured using an ion chromatograph (ICS-300, manufactured by Dionex Corporation). For the measurement, an IonPac CS14 cation molecule column and 10 mmol / L metasulfonic acid (both manufactured by Dionex Corporation) were used as the eluent.
[0050] [Measurement of absorbance of filtrate] 1.0 g or 2.0 g of the dried powder sample obtained in the examples was accurately weighed and dissolved in 8 times its mass (8.0 g or 16.0 g) of water at 25°C. The solution was then filtered using a membrane filter (DISMIC-25HP, manufactured by Toyo Roshi Co., Ltd., with a mesh size of 0.20 μm). The amount of insoluble fine particles that passed through the membrane filter and migrated to the filtrate from the sparingly soluble components in the resulting filtrate was qualitatively evaluated by measuring the absorbance at a wavelength of 660 nm using a UV-Vis spectrophotometer (UV-1800, manufactured by SHIMADZU Co., Ltd.). A quartz cell (10 mm × 10 mm × 45 mm) was used for the measurement, and the measurement was performed at 25°C. [Volume-based cumulative 50% particle size] The volume-based particle size distribution of a dried powder sample was measured using a laser diffraction scattering particle size distribution analyzer (HELOS & RODOS (airflow-type dispersion module) manufactured by SYMPATEC) at a dispersion pressure of 5 bar, and the volume-based cumulative 50% particle size (D50) was determined.
[0051] [Moisture content] The moisture content of the dried powder sample was measured by coulometric titration using a Karl Fischer moisture meter (HIRANUMA Corporation, AQS-225010S). The water vaporization temperature was set to 100°C, and nitrogen gas was used as the carrier gas. Aqualight RS-A (HIRANUMA Corporation) was used as the generating solution, and Aqualight CN (HIRANUMA Corporation) was used as the counter electrode.
[0052] [X-ray diffraction measurement] X-ray diffraction measurements were performed on the dried powder sample using an X-ray diffraction analyzer (Shimadzu Corporation, XRD-6100) under the following measurement conditions. Tube:Cu Tube voltage: 40kV Tube current: 30mA Divergence slit: 1.0° Scattering slit: 1.0° Light-receiving slit: 0.3mm Scan speed: 2.0° / min Step width: 0.02°
[0053] [Example 1] 82.0 g of deionized water (resistivity: 17.2 MΩ·cm), 288.6 g of 28% by mass aqueous ammonia, 1424.0 g of 35% by mass aqueous hydrogen peroxide, 33.8 g of lithium hydroxide monohydrate (LiOH·H2O), and 166.7 g of hydrated niobium oxide (Nb2O5·nH2O, n=4.6, Nb2O5 content: 76.4% by mass) were added to a 5 L beaker, and the mixture was mechanically stirred at 60°C for 10 hours. The resulting solution was filtered through 0.5 μm mesh filter paper to obtain an aqueous solution containing the niobium complex and lithium, which was used as the starting material solution for lithium niobate. The concentrations of niobium and lithium in the obtained starting material solution for lithium niobate were 4.41% by mass and 0.38% by mass, respectively, and the molar ratio of Li / Nb was 1.15. Furthermore, the concentration of ammonium ions in the aforementioned raw material solution was measured to be 960 ppm. Additionally, the absorbance of the precursor solution at a wavelength of 660 nm was measured to be 0.001.
[0054] 114.2 g of the raw material solution prepared under the above conditions was divided into containers, and these containers were placed in a vacuum dryer. The containers were kept at 25°C and maintained at a gauge pressure of -0.1 MPa or less for 12 hours to obtain a dried product. The gauge pressure is the pressure difference between the pressure inside the vacuum dryer and atmospheric pressure. Subsequently, the dried product was crushed in a mortar to obtain 9.9 g of dried powder. The volume-based particle size distribution of the crushed dried powder was measured using a laser diffraction particle size distribution analyzer, and the cumulative 50% particle size D was found to be 50 It was 140 μm. X-ray diffraction measurements of the dried powder after crushing revealed a halo pattern in the 2θ:20°~60° region, and since almost no peaks originating from lithium niobate (LiNbO3) crystals were observed, it can be concluded that the dried powder obtained in this example is mainly composed of amorphous materials. Furthermore, 2.0 g of the dried powder was placed in a muffle furnace and heat-treated at 600°C in an air atmosphere for 2 hours, after which it was crushed in a mortar to obtain 1.3 g of calcined powder. X-ray diffraction measurements of the obtained calcined powder revealed peaks originating from lithium niobate (LiNbO3) crystals, confirming that the dried powder is a precursor of lithium niobate.
[0055] A 6.4 mg sample was taken from the dried powder and subjected to TG-DTA analysis in an N2 atmosphere at a flow rate of 200 mL / min and a heating rate of 10 °C / min from 30 °C to 120 °C. An endothermic peak, presumably the decomposition temperature of the niobium complex, was observed at 70 °C, indicating that the above drying temperature is below the decomposition temperature of the niobium complex. When the dried powder was measured by FT-IR, a peak of 845 cm² attributed to the niobium complex was observed. -1 ±20cm -1The presence of a peak confirmed that the dried powder contained a niobium complex. The metal elements contained in an aqueous solution of the dried powder dissolved in hydrofluoric acid were measured by ICP-AES according to the above-mentioned [Measurement of Niobium and Lithium Content]. The niobium and lithium content in the dried powder were found to be 47.20% by mass and 3.47% by mass, respectively.
[0056] The molar ratio of Li / Nb was 0.98. From the above measurement results, it was confirmed that the dried powder is a powder containing a niobium complex and lithium, and that the proportion of niobium among the metal elements contained in the dried powder is 0.932 by mass ratio. Furthermore, from the niobium content and lithium content in the dried powder, it was determined that Nb HF and Li HF The following can be calculated. The dried powder is dissolved in water according to the above [evaluation of water solubility], filtered, and the metal elements contained in the filtrate are measured by ICP-AES to determine Nb W and Li W By measuring the dissolved niobium and lithium in water, we calculated that 86.2% of the niobium and 99.9% of the lithium dissolved in the water.
[0057] Table 1 shows the various measurement results for the dried powder obtained in this embodiment. When the dried powder obtained in this embodiment is dissolved in water again, an aqueous solution containing niobium complex and lithium with almost the same composition as the precursor solution before solidification is obtained. Therefore, the powder containing niobium complex and lithium obtained by the manufacturing method of the present invention is a powder with high solubility in water, suitable for preparing a precursor solution of lithium niobate for coating the surface of the positive electrode active material particles of a lithium-ion secondary battery with lithium niobate, which is a solid electrolyte. Furthermore, it is found that by storing the powder containing niobium complex and lithium obtained by the manufacturing method of the present invention, the problems of storage stability and reduction of transportation costs of aqueous solutions containing the precursor of lithium niobate are resolved.
[0058] [Comparative Example 1] 505.7 g of an aqueous solution prepared under the same conditions as in Example 1 was placed in a container, and the container was then placed in a shelf-type dryer and dried under air at 120°C for 12 hours to obtain a dried product. The dried product was then crushed in a mortar to obtain 43.1 g of dried powder. When the dried powder was measured by FT-IR, a concentration of 845 cm² was found to be attributed to the niobium complex. -1 ±20cm -1 Since no peak was observed, it was confirmed that the dried powder did not contain niobium complex. Table 1 shows the results of various measurements for the dried powder obtained in this comparative example. It can be seen that the dried powder of this comparative example, which does not contain a niobium complex, has inferior water solubility compared to the example. [Table 1]
Claims
1. A powder containing a niobium complex and lithium, the powder containing niobium in an amount of 25% by mass or more and 75% by mass or less, a mass ratio of niobium to all metal elements contained in the powder of 0.775 or more and 0.950 or less, and a niobium dissolution rate of the powder containing a niobium complex and lithium, defined by the following formula (1), of 80% or more: Niobium dissolution rate (%) = Nb w ×100 / Nb HF …(1) where Nb w and Nb HF is the mass of niobium calculated by the following procedure. A powder containing a niobium complex and lithium is weighed, and the weighed powder is dissolved in water at 25°C in an amount 8 times the mass of the powder. The solution is then filtered through a membrane filter with a mesh size of 0.20 μm, and the concentration of niobium in the resulting filtrate is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of niobium dissolved in the filtrate per unit mass of the weighed powder, calculated from the niobium concentration in the filtrate and the mass of the filtrate, is called Nb w Let's say. A powder containing a niobium complex and lithium is weighed, and hydrofluoric acid is added to the weighed powder to dissolve it. After cooling, the concentration of niobium in the resulting solution is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of niobium contained per unit mass of the weighed powder, calculated from the niobium concentration in the resulting solution and the volume of the solution, is defined as Nb HF Let's say.
2. The powder containing a niobium complex and lithium according to claim 1, wherein the powder contains 40% by mass or more and 50% by mass or less of niobium.
3. 3. The powder containing a niobium complex and lithium according to claim 1 or 2, wherein the powder contains 2.5 mass% or more and 6.0 mass% or less of lithium, the total proportion of niobium and lithium among the metal elements contained in the powder is 0.80 or more and 1.00 or less in mass ratio, and the molar ratio of Li / Nb is 0.7 or more and 1.5 or less.
4. The powder containing the niobium complex and lithium according to any one of claims 1 to 3, wherein the powder contains 3.0 mass% or more and 4.5 mass% or less of lithium.
5. The powder containing a niobium complex and lithium according to any one of claims 1 to 4, wherein when the powder is dissolved in 8 times the mass of water at 25°C, the powder containing a niobium complex defined by the following formula (2) and lithium has a lithium solubility of 80% or more: Lithium dissolution rate (%) = Li w ×100 / Li HF …(2) Here, Li w and Li HF is the mass of lithium, calculated by the following procedure: A powder containing a niobium complex and lithium is weighed, and the weighed powder is dissolved in water at 25°C in an amount 8 times the mass of the powder. The solution is then filtered through a membrane filter with a mesh size of 0.20 μm, and the lithium concentration in the resulting filtrate is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of lithium eluted into the filtrate per unit mass of the weighed powder, calculated from the lithium concentration in the filtrate and the mass of the filtrate, is defined as Li w Let's say. A powder containing a niobium complex and lithium is weighed, hydrofluoric acid is added to the weighed powder to dissolve it, and the solution is cooled. The lithium concentration in the resulting solution is measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The mass of lithium contained per unit mass of the weighed powder, calculated from the lithium concentration in the resulting solution and the volume of the solution, is Li HF Let's say.
6. The powder containing a niobium complex and lithium according to any one of claims 1 to 5, wherein the powder contains oxygen and the total content of niobium, lithium and oxygen is 85 mass% or more.
7. The powder containing the niobium complex and lithium according to any one of claims 1 to 6, wherein the powder is dissolved in 8 times the mass of water at 25°C and then filtered through a membrane filter having an opening of 0.20 µm, and the content of ammonium ions contained in the obtained filtrate is 0.5 mass% or less.
8. The powder containing the niobium complex and lithium according to any one of claims 1 to 7, wherein the powder is dissolved in 8 times the mass of water at 25°C and then filtered through a membrane filter having a mesh size of 0.20 µm, and the resulting filtrate has an absorbance of 1.0 or less at a wavelength of 660 nm.
9. Volume-based cumulative 50% particle size D 50 A powder containing lithium and the niobium complex according to any one of claims 1 to 8, wherein the particle size is 1 mm or less.
10. a step of mixing a niobium compound, a lithium compound, an alkali, hydrogen peroxide, and water to obtain an aqueous solution containing a niobium complex and lithium; drying the aqueous solution containing the niobium complex and lithium at a temperature equal to or lower than the decomposition temperature of the niobium complex; A method for producing a powder containing a niobium complex and lithium, comprising:
11. The method for producing a powder containing a niobium complex and lithium according to claim 10, wherein the pressure during drying of the aqueous solution is equal to or lower than the saturated vapor pressure of water at the drying temperature of the aqueous solution.
12. a step of dissolving the powder containing the niobium complex and lithium obtained by the production method according to claim 10 or 11 in water to obtain an aqueous solution containing the niobium complex and lithium; a step of coating a surface of a positive electrode active material for a lithium secondary battery with an aqueous solution containing the niobium complex and lithium; a step of subjecting the lithium secondary battery positive electrode active material coated with the aqueous solution containing the niobium complex and lithium to a heat treatment; The present invention relates to a method for producing an active material for a lithium secondary battery having a coating layer containing lithium niobate, the active material comprising: